Emerging role of mesenchymal stem cell-derived extracellular vesicles in oral and craniomaxillofacial tissue regenerative medicine - Liu, Meng; Liu, Xin; Su, Yuting; Li, Shijie; Chen, Yuan; Liu, Anqi; Guo, Jing; Xuan, Kun; Qiu, Xinyu (Frontiers in Bioengineering and Biotechnology, 2022)
Mesenchymal stem cells (MSCs) are multipotent stem cells with differentiation potential and paracrine properties, drawing significant attention in the field of regenerative medicine. Extracellular vesicles (EVs), mainly including exosomes, microvesicles and apoptotic bodies (ABs), are predominantly endosomal in origin and contain bioactive molecules, such as miRNAs, mRNAs, and proteins, which are transferred from their original cells to target cells. Recently it has emerged that MSC-derived EVs (MSC-EVs) combine the advantages of MSCs and EVs, which may be used as a promising MSC-based therapy in tissue repair and regeneration. Oral and craniomaxillofacial diseases are clinically complications containing the soft and hard tissues in craniofacial and dental arches. These diseases are often induced by various factors, such as chemical, microbiological, physical factors, and systemic disorders. For decades, tissue repair and regeneration in oral and craniomaxillofacial regions provide substantial improvements in the prevention and treatment of some severe diseases. In this review we discuss MSC-EVs and their therapeutic potential in oral and craniomaxillofacial tissue regenerative medicine.